2021
DOI: 10.1002/hbm.25416
|View full text |Cite
|
Sign up to set email alerts
|

The frontotemporal organization of the arcuate fasciculus and its relationship with speech perception in young and older amateur singers and non‐singers

Abstract: The ability to perceive speech in noise (SPiN) declines with age. Although the etiology of SPiN decline is not well understood, accumulating evidence suggests a role for the dorsal speech stream. While age‐related decline within the dorsal speech stream would negatively affect SPiN performance, experience‐induced neuroplastic changes within the dorsal speech stream could positively affect SPiN performance. Here, we investigated the relationship between SPiN performance and the structure of the arcuate fascicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 131 publications
(195 reference statements)
4
23
1
Order By: Relevance
“…While it is possible that amateur singing does not in uence SPiN to the same extent as musical instrument playing, it is also possible that the effect of musical activities on SPiN follows a dosedependent relationship, with more intense or more frequent practice being associated with increased bene ts. This is consistent with the ndings that, compared to non-musicians, both amateur singers and professional instrumentalists exhibit differences in the function or structure of the dorsal speech stream, but that these differences were associated to a SPiN advantage only in professionals, not in amateurs (Du and Zatorre 2017;Perron et al 2021). The notion of a dose-dependent effect of musical practice on SPiN is also consistent with the literature on music-induced plasticity, which shows that differences in brain anatomy between instrumentists and non-musicians are related to several practice-related behaviours, such that increased plasticity is related to lower age of onset of musical practice, a higher number of years of practice, a higher number of weekly hours of practice, etc.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…While it is possible that amateur singing does not in uence SPiN to the same extent as musical instrument playing, it is also possible that the effect of musical activities on SPiN follows a dosedependent relationship, with more intense or more frequent practice being associated with increased bene ts. This is consistent with the ndings that, compared to non-musicians, both amateur singers and professional instrumentalists exhibit differences in the function or structure of the dorsal speech stream, but that these differences were associated to a SPiN advantage only in professionals, not in amateurs (Du and Zatorre 2017;Perron et al 2021). The notion of a dose-dependent effect of musical practice on SPiN is also consistent with the literature on music-induced plasticity, which shows that differences in brain anatomy between instrumentists and non-musicians are related to several practice-related behaviours, such that increased plasticity is related to lower age of onset of musical practice, a higher number of years of practice, a higher number of weekly hours of practice, etc.…”
Section: Introductionsupporting
confidence: 89%
“…This notion is in line with the Overlap, Precision, Emotion, Repetition, Attention (OPERA) hypothesis (Patel 2014(Patel , 2012(Patel , 2011, which suggests that musical activities affect speech skills by driving plasticity within speech networks when musical practice is frequent. In our previous study (Perron et al 2021), although we found that the number of years of continuous singing was associated to a small extent with the structure of the arcuate fasciculus, we did not identify a relationship between the number of years of continuous singing and SPiN. However, several other singing practice behaviours, such as frequency of singing, duration of choral practice, age at onset of singing, etc., could drive plasticity within auditory and dorsal speech stream regions and, in turn, lead to better SPiN performance.…”
Section: Introductioncontrasting
confidence: 72%
See 1 more Smart Citation
“…All participants provided informed consent and received a small monetary compensation for their participation. Behavioural and diffusion MRI collected as part of this project have been published elsewhere (Perron et al 2021). e Health = self-reported general health status on a scale of 0 to 7, with 0 being the lowest health level and 7 the maximal one.…”
Section: Participantsmentioning
confidence: 99%
“…A negative value of c indicates a bias toward responding "identical" whereas a positive value of c represents a bias towards responding "different". A value of zero indicates the absence of bias.Since we previously reported no difference in SPiN performance between the singers and the non-singers in the two noise conditions for sensitivity (d')(Perron et al 2021), here we averaged the two conditions of noise for each metric (mean accuracy, d', c, RT). For each dependent variable (mean accuracy, d', c, RT), normality was assessed via visual inspection of histograms and Q-Q plots and the homogeneity of variance was assessed using Levene's test (p ≥ .05).…”
mentioning
confidence: 99%